2021
DOI: 10.3390/ani11092666
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Horse Age, Marinating Substances, and Frozen Storage on Horse Meat Quality

Abstract: The present study analyzed the influence of horse age, substances used for marinating, and frozen storage on the quality of horse meat. It was conducted on the samples of the longest thoracic muscle, obtained from 12 carcasses of horses (aged 4–7 and 8–12 years). Among the analyzed samples, a higher fat content (p < 0.05) was found in the meat obtained from the carcasses of older horses. The pH value of the meat samples was influenced by the treatment applied (p < 0.05). Of the substances used for marina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…We detected high levels of icilin in Pingliang Red Cattle and crossbred Wagyu cattle, suggesting that icilin functions in IMF formation. The high content of malic acid in the muscles of Pingliang Red Cattle and Wagyu cross F1 generation lowers the pH, consequently reducing the shear . Phosphoric acid, produced by the breakdown of ATP, is intricately related to the freshness of fish and is a candidate marker of fish freshness, explaining the significant positive correlation between phosphoric acid and DAA and SAA in this study.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…We detected high levels of icilin in Pingliang Red Cattle and crossbred Wagyu cattle, suggesting that icilin functions in IMF formation. The high content of malic acid in the muscles of Pingliang Red Cattle and Wagyu cross F1 generation lowers the pH, consequently reducing the shear . Phosphoric acid, produced by the breakdown of ATP, is intricately related to the freshness of fish and is a candidate marker of fish freshness, explaining the significant positive correlation between phosphoric acid and DAA and SAA in this study.…”
Section: Discussionmentioning
confidence: 51%
“…The high content of malic acid in the muscles of Pingliang Red Cattle and Wagyu cross F1 generation lowers the pH, consequently reducing the shear. 41 Phosphoric acid, produced by the breakdown of ATP, is intricately related to the freshness of fish and is a candidate marker of fish freshness, 42 explaining the significant positive correlation between phosphoric acid and DAA and SAA in this study. In addition, we speculate that phosphoric acid can improve Pingliang Red Cattle tenderness through indirect mechanisms that improve nutrient metabolism and delay anaerobic digestion.…”
Section: ■ Discussionmentioning
confidence: 61%
“…The elevated myoglobin concentration in horsemeat facilitates its colour transformation, rendering it more visible to the eye compared to pork or veal, and, thus, fresh horsemeat colour stability is relatively low, shortening the shelf-life (Lorenzo et al, 2014(Lorenzo et al, , 2019Stanisławczyk et al, 2021a). It has been reported that horsemeat darkens as the animal ages, while the fat tissue turns yellowish or even orange in colour (Stanisławczyk et al, 2021b). However, the myoglobin content in horse muscle tissue increases during the first years two of life, and then decreases during the ten following years (Lorenzo et al, 2019).…”
Section: Meat Qualitymentioning
confidence: 99%
“…Horsemeat texture is undesirable, as it exhibits extreme stringiness and hardness, particularly in older animals, even after undergoing heat treatment (Stanisławczyk et al, 2021a). This can be attributed to a higher proportion of connective tissue, specifically collagen (3.5% of the total protein content in horsemeat), compared to pork (less than 0.5%) and beef (ranges from 0.49% to 1.0%) (Stanisławczyk et al, 2021a(Stanisławczyk et al, , 2021b. Conversely, horsemeat from younger animals generally displays superior tenderness, surpassing in this aspect other meat types, especially, beef (Lorenzo et al, 2014(Lorenzo et al, , 2019Stanisławczyk et al, 2021a).…”
Section: Meat Qualitymentioning
confidence: 99%
See 1 more Smart Citation